Human cytomegalovirus infection in humanized liver chimeric mice. Issue 6 (26th February 2013) - Kawahara, Toshiyasu; Lisboa, Luiz Filipe; Cader, Sonia; Douglas, Donna N.; Nourbakhsh, Mahra; Pu, Christopher H.; Lewis, Jamie T.; Churchill, Thomas A.; Humar, Atul; Kneteman, Norman M.
<x xml:space="preserve">Abstract</x> Aim Cytomegalovirus is a common viral pathogen that influences the outcome of organ transplantation. To date, there is no established method to evaluate the effects of human CMV (HCMV) treatments in vivo except for human clinical trials. In the current study, we describe the development of a mouse model that supports the in vivo propagation of HCMV. Methods One million viable human hepatocytes, purified from human livers, were injected into the spleens of severe combined immunodeficient/albumin linked‐urokinase type plasminogen activator transgenic mice. A clinical strain of HCMV was inoculated in mice with confirmed human hepatocyte engraftment or in non‐chimeric controls. Infection was monitored through HCMV titers in the plasma. Mice were administrated ganciclovir (50 mg/kg per day, i.p.) beginning at 2 days post‐HCMV inoculation, or human liver natural killer (NK) cells (20 × 106 cells/mouse, i.v.) 1 day prior to HCMV inoculation. Results Chimeric mice that received HCMV showed high plasma titers of HCMV DNA on days 1 and 6 that became undetectable by day 11 post‐inoculation. In contrast, non‐transplanted mice had only residual plasma inoculum detection at day 1 and no detectable viremia thereafter. The levels of HCMV DNA were reduced by ganciclovir treatment or by human liver NK cell adoptive transfer, while HCMV‐infected chimeric mice that were not treated sustained viremia during the follow up. Conclusion Human liver chimeric mice provide an in vivo model for the study of acute HCMV infection of hepatocytes.